Human Investment Orientation in Islamic Education Marketing Islamic Perspective - Hernawati, Sari; Hafizh, Muhammad; Astuti, Widia (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
In contrast to the non-profit nature of Islamic Education and its concentration on developing human resources as a human investment in the future, the problem in this article is that advertisement in the world of business-oriented education is very focused on earning profits and, at times, for the private benefit of officials in Islamic Education institutions. In this article, qualitative literary analyses are used as a research method, and the data sources are various types of literatures, includes books and studies of science. In order to address the phrasing of the problem stated, descriptive analysis of the data is performed. The results showed that human investment in marketing activities for Islamic education services has an influence because it can provide guarantees for improving the quality of human resources for consumers so that marketing can run ideally. Human investment includes increasing intelligence, skills, talents, and abilities to be useful for society, nation and state so that the orientation of education in marketing activities is oriented to increase human resources.